2020
DOI: 10.1021/acsaem.0c01265
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Generation and CO2 Conversion Using g-C3N4 Decorated Dendritic Fibrous Nanosilica: Role of Interfaces between Silica and g-C3N4

Abstract: We have synthesized g-C3N4 decorated over dendritic fibrous nanosilica (DFNS). The generation of C–N–Si interfaces by coating each fiber of DFNS with g-C3N4 not only provided high surface area but also affected the optical and electronic properties of the composite. The catalyst synthesis reproducibility issue of g-C3N4 was resolved using a vacuum-sealed quartz tube. The extended light absorption in the visible region, enhanced lifetime of photogenerated charge carriers due to the formation of interfaces betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Two weak signals at 0.4 and 1.0 ppm can be ascribed to a little alkane species of the internal standard (silicone grease). The peaks at 4.6, 6.7, and 8.8 ppm should be due to adsorbed H 2 O, alkene species, and amino 27,28 present in g-C 3 N 4 , respectively. After coupling with TiO 2 , the Photocatalytic Performance.…”
Section: ■ Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two weak signals at 0.4 and 1.0 ppm can be ascribed to a little alkane species of the internal standard (silicone grease). The peaks at 4.6, 6.7, and 8.8 ppm should be due to adsorbed H 2 O, alkene species, and amino 27,28 present in g-C 3 N 4 , respectively. After coupling with TiO 2 , the Photocatalytic Performance.…”
Section: ■ Discussion and Resultsmentioning
confidence: 99%
“…On the other hand, heterogeneous catalysis always occurs on the catalyst surface, so molecular adsorption plays an important role in the catalytic reaction. It has been found that it is difficult for pure g-C 3 N 4 to adsorb H 2 O, which obviously decreases the H 2 O interaction with photogenerated electrons to produce H 2 on the g-C 3 N 4 surface. Anatase TiO 2 (especially the {101} facet) can adsorb H 2 O effectively, which can create a connected film of H 2 O to increase the mobility of the H + . , As such, close coupling of g-C 3 N 4 with TiO 2 may constrain abundant H 2 O on the interface of the TiO 2 /g-C 3 N 4 catalyst to accelerate the H 2 O reaction with photogenerated carriers on g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 presents the Z-scheme charge transfer pathway of the Ag 3 PO 4 /g-C 3 N 4 composite photocatalyst for the degradation of organic pollutants. The bandgap of g-C 3 N 4 was 2.7 eV with the VB potential of ~ 1.4 eV and CB potential of ~ −1.3 eV [ 27 , 28 ]. The potential of e − on the CB of g-C 3 N 4 was −1.3 eV, which can reduce the molecular oxygen O 2 to·O 2 because the potential of O 2 /·O 2 – was −0.44 eV vs. NHE.…”
Section: Resultsmentioning
confidence: 99%
“…In plasmon-driven CO 2 reduction reaction (CO 2 RR) on Ag nanoparticles (NPs), for which we recently developed in-situ single-NP level monitoring, , we observe similar NP-to-NP heterogeneity in the profile of species produced. However, the heterogeneity observed here, we argue, is a reflection of the inherent stochasticity (noise) in catalytic events taking place on the NPs.…”
Section: Introductionmentioning
confidence: 96%